Behaviors in hybrid state systems - (:unkn) unknown (International Information and Engineering Technology Association, 1998)
Hybrid state systems (HSS) are modeled as a combination of Discrete State (DSS) and Continuous State Systems (CSS). The continuous state space can be divided into regions so that in every region depending on the discrete state of HSS the continuous state system dynamic functions are found. An example is provided and some behaviors not encountered in classical (discrete or continuous state) dynamic systems are observed and studied in hybrid state systems.
Keywords: Discrete and continuous state space; Hybrid systems; Modeling